Drying kinetics of dried injera (dirkosh) using a mixed-mode solar dryer. Issue 1 (1st January 2021) - Sileshi, Senay Teshome; Hassen, Abdulkadir Aman; Adem, Kamil Dino
Abstract: Injera is a staple food for Ethiopians both in the country and abroad. Injera has high nutritional value as it is reach in fibre and other nutrients most importantly it is gluten free. Dried injera ( dirkosh ) is mostly preserved using open sun drying. But there is no study conducted to improve the drying process and evaluate dried injera ( dirksoh ) for its drying kinetics and performance of the solar dryer. This is the first attempt to formulate the drying kinetics of dried injera . Thus, a mixed mode natural convection solar dryer was designed, manufactured and tested using injera ( dirkosh ) in Addis Ababa, Ethiopia. The test result indicated that the drying efficiency and overall drying rate were 17.7% and 3.69 × 10 −5 kg/s, respectively. The moisture content of injera was reduced from 65.5% to 12% in wet basis in 4 h in the solar dryer. Statistical analyses of the result have shown that Midilli and Verma as a best fit models with the highest value of the correlation coefficient ( R 2 ) and the lowest values of reduced chi-square ( χ 2 ) and root mean square error (RMSE). Finally, it was concluded that solar drying of injera could be a feasible method for preserving and maintaining the quality of dried injera ( dirkosh ) with a minimum cost.